Use these "Agents" for Best Recoveries - Hercules Incorporated (1952 Hercules Advertisements, 1952)
Advertisement for flotation (also known as frothing) agents, including pine oil and rosin amine, manufactured and sold by the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Rosin oil; Chemical industry; Hercules Incorporated; Pine oil; Corporations; Naval stores; Flotation reagents; Advertising, Industrial